Detoxification enzymes associated with butene‐fipronil resistance in Epacromius coerulipes. Issue 1 (14th August 2019) - Jin, Yongling; Gao, Yugang; Zhang, Haiyan; Wang, Liyan; Yang, Kejun; Dong, Hui
Abstract: BACKGROUND: Epacromius coerulipes is a widely distributed locust pest species. Chemical control is the main method used to kill locusts; however, this can result in the selection of locusts with resistance to chemical pesticides. Therefore, the study of resistance is of great significance for the sustainable management of locusts. RESULTS: In this study, to investigate the relationship between detoxification enzymes and butene‐fipronil resistance in E. coerulipes, resistant strains of the locust were compared with sensitive strains. The synergism of synergistic agents was significantly enhanced, and the activities of multifunctional oxidase, carboxylesterase, and glutathione sulfur transferase were significantly increased. Transcriptome sequencing revealed 226 detoxification enzyme genes and 23 upregulated genes. Neighbor‐joining was used to construct a phylogenetic tree of related gene families, which included 59 P450 genes, 52 carboxylesterases (CarE) genes, and 25 glutathione S ‐transferase (GST) genes. Reverse transcription polymerase chain reaction (RT‐PCR) analysis results of overexpressed genes in the resistant population combined with a phylogenetic tree showed that four P450 genes belonged to the CYP6, CYP4, CYP18 and CYP302 families, two CarE genes belonged to Clade A families, and one GST gene belonged to the Sigma family. These family members were annotated as detoxification enzyme genes of metabolic insecticide in the transcriptome databases. CONCLUSIONS: This study showed that P450, CarE and GST together resulted in moderate resistance to butene‐fipronil in locusts. The analysis revealed several overexpressed detoxification enzyme genes that will be the focus of future studies on the mechanism of resistance to butene‐fipronil. © 2019 Society of Chemical Industry Abstract : Detoxification enzyme genes were systematically classified. Eleven upregulated sequences were analyzed using RT‐PCR. Resistance of Epacromius coerulipes to butene‐fipronil was related to detoxifying enzyme genes.